Relationship of general self‐efficacy with anxiety, symptom severity and quality of life in cancer patients before and after radiotherapy treatment. Issue 5 (21st May 2012) - Mystakidou, Kyriaki; Tsilika, Eleni; Parpa, Efi; Gogou, Pinelopi; Panagiotou, Irene; Vassiliou, Ioannis; Gouliamos, Athanasios
Abstract Purpose Treatment‐related symptoms can increase psychological and physical distress and alter the patient's quality of life. The present study evaluates prospectively treatment‐related symptoms, general self‐efficacy, anxiety and quality of life (QoL) in patients with different types of cancer undergoing external beam radiotherapy (RT) and the relationship of patients' general self‐efficacy with the assessed measures, at the baseline and their absolute change 1 month after the end of the treatment. Methods The sample consisted of 90 cancer patients. General self‐efficacy was assessed using the General Perceived Self‐efficacy (GSE). QoL was evaluated using the Linear Analogue Scale Assessment (LASA), anxiety with the Anxiety subscale of the Hospital Anxiety and Depression (HAD) scale, whereas symptom severity and interference were assessed using the MD Anderson Symptom Inventory (MDASI). The instruments were administered first at the beginning of the RT and then 1 month after the completion of the RT. Results At post‐treatment, general self‐efficacy was reduced (28.86 ± 6.42), anxiety scores were elevated (9.56 ± 4.42), QoL scores were reduced (6.74 ± 1.81) and symptoms severity were deteriorated (3.24 ± 2.62). Pre‐treatment and post‐treatment absolute change scores revealed statistically significant negative correlations between general self‐efficacy absolute scores and anxiety (p < 0.0005). Moderate negative correlations between general self‐efficacy absolute scores and symptoms (MDASI symptom severity: p = 0.003, symptom interference: p = 0.002), whereas a low positive correlation was found between general self‐efficacy absolute scores and LASA energy scale (p = 0.048). Conclusions A sense of self‐efficacy and its relationship with anxiety, symptom distress and quality of life are important factors for patients receiving radiotherapy. Health care professionals need to be aware of anxiety, symptom severity and patient's quality of life prior to treatment initiation. Copyright © 2012 John Wiley & Sons, Ltd.